Bosnia and Herzegovina : BCBS - IADI Core Principles for Effective Deposit Insurance Systems Technical Note - World Bank; International Monetary Fund (World Bank, Washington, DC, 2015)
This Technical Note was prepared in the context of a joint World Bank-IMF Financial Sector Assessment Program mission in Bosnia and Herzegovina during October – November, 2014. The FSAP team found the DIA is to be Compliant or Largely Compliant with 12 out of 16 applicable Core Principles and Materially Non-Compliant with three Core Principles. The team found a number of areas where some deficiencies exist in the deposit insurance system and financial safety-net arrangements and accordingly is proposing a corrective action plan to address these areas.